Hidroxiapatita sintética associada a fatores de crescimento em subcutâneo de orelha externa de coelho (Oryctolagus cuniculus) - Silva, Juliana Martins da (2006)
The aim of this research was to evaluate the synthetic hydroxyapatite (HA) as a carrier by bovine bone morphogenetic protein (BMP), platelet-rich plasma (PRP) and bone marrow (BM) in the ectopic bone formation in a rabbit model. Two tunnels were made in the subcutaneous tissue of external face of each ear in the rabbit, opened in the end a scarified a large room to insert five types of associations of biomaterials: HA+BMP, HA+MO, HA+BMP+MO, HA+PRP and HA+BMP+PRP. In 30 and 45 days postimplantations, biopsies were made to light microscopy evaluation. All implants of these biomaterials were biocompatibility with subcutaneous ear tissue of rabbit, as well as the resorption of these materials implants occurred slowly and were mediated by giant cells. The PRP plus BMP and HA was better than others bioresorble materials. The neovascularization occurred in little ratio and in implants with HA+PRP and HA+BMP+PRP was larger. It was possible to conclude that HA associated with BMP and PRP and HA plus BMP could produce ectopic bone formation in subcutaneous ear tissue of rabbits.